1980
DOI: 10.1017/s0022377800022443
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model of plasma double layers using the Vlasov equation

Abstract: The one-dimensional plasma double layer is modelled by numerically integrating the time-dependent Vlasov and Poisson equations. A constant magnetic field at an arbitrary angle with respect to the layer is included. The model shows that such a plasma region can generate as well as reflect Langmuir waves and shows how RF emission may arise. An axial magnetic field does not inhibit the formation of a double layer, although a non-axial field may do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The front of the beam becomes unstable in exactly the same manner as was found in the particle simulation of Sakanaka (1972), which finally results in the sub-structure of an ion hole which is superimposed on the double layer. The onset of such a secondary ion trapping is also seen in the computer output of Johnson (1980) who followed the time-dependence and stability of double layers. There is therefore no doubt that electron and ion holes do exist.…”
Section: Introductionmentioning
confidence: 86%
“…The front of the beam becomes unstable in exactly the same manner as was found in the particle simulation of Sakanaka (1972), which finally results in the sub-structure of an ion hole which is superimposed on the double layer. The onset of such a secondary ion trapping is also seen in the computer output of Johnson (1980) who followed the time-dependence and stability of double layers. There is therefore no doubt that electron and ion holes do exist.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, the application of a potential drop across a collisionless plasma may drive a double layer along with a host of other plasma processes (Singh and Schunk, 1982a). There are several laboratory experiments (Coakley and Hershkowitz, 1979;Iizuka et al, 1983Iizuka et al, , 1985 and numerical simulations (Joyce and Hubbard, 1978;Singh, 1980Singh, , 1982Singh and Thiemann, 1980a,b;Singh andSchunk, 1982a,c, 1983a;Johnson, 1980) in which DL'shave been driven by applied potential drops. Some of these experiments and simulations (Singh, 1982;Singh andSchunk, 1982a, 1983a) show remarkable similarities in both the processes leading to the formation of a DL and its dynamics.…”
Section: Applied Potential Dropmentioning
confidence: 99%
“…The suggestion that such electric fields parallel to the magnetic field occur in space plasmas reactivated research on double layers [Block, 1972[Block, , 1978Mozer et al, 1977;Shawhan et al, 1978]. A series of laboratory experiments [Lutsenko et al, 1975[Lutsenko et al, , 1976Quon and Wong, 1976;Coakley et al, 1978;Coakley and Hershkowitz, 1979;Leung et al, 1980;Torven and Lindberg, 1980;Baker et al, 1981] and numerical simulations [Goertz and Joyce, 1975;Joyce and Hubbard, 1978;Hubbard and Joyce, 1979;Singh, 1979Singh, , 1980Singh, , 1981Singh and Thiernann, 1980a, b;Johnson, 1980;Wagner et al, 1980;Sato and Okuda, 1981] have confirmed the formation of double layers in plasmas under different conditions and have shed some light on their dynamics and stability.…”
Section: Introductionmentioning
confidence: 99%